2014
DOI: 10.1111/jhn.12232
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic responses of stapleSouthAsian foods alone and combined with curried chicken as a mixed meal

Abstract: Adding fat and protein-containing curries as part of a mixed meal to carbohydrate rich staple foods reduced glycaemic responses, and also changed the GI category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Examining the impact of mixed meals on glycemic responses of rice is important, as any effective method that blunts glycemic excursions deserves to be advocated to the public. Previous studies have demonstrated that the glycemic responses can be manipulated when eaten as mixed meals due to the differential impact of the macronutrients and fiber content of the meal as a whole [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Examining the impact of mixed meals on glycemic responses of rice is important, as any effective method that blunts glycemic excursions deserves to be advocated to the public. Previous studies have demonstrated that the glycemic responses can be manipulated when eaten as mixed meals due to the differential impact of the macronutrients and fiber content of the meal as a whole [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…One of the studies showed that the intake of chicken with white rice can reduce the postprandial GR compared to consuming white rice alone. 16 In this study, the chicken was prepared in a curry sauce. Another study also tested steamed chicken with rice, which also shows a reduction in GR.…”
Section: Resultsmentioning
confidence: 99%
“…International Standard-ISO 26642 asserts a minimum of ten participants is enough to determine the GI value (19); accordingly, 16 participants were considered (19,22,(25)(26)(27)(28). Then IAUC and GI values were calculated using Microsoft Excel ® 2010, the results were expressed as means with standard error of the mean (SEM).…”
Section: Discussionmentioning
confidence: 99%